Porcupining : a prickly love story - Wheeler, Lisa, 1963-; Bynum, Janie (Boston [Mass.] : Little, Brown and Co., 2002)
After a series of rejections, a lonely porcupine finds true love with a prickly hedgehog.
"Megan Tingley books."
Keywords: Porcupines -- Fiction; Hedgehogs -- Fiction